Peningkatan Kepedulian Lingkungan melalui Kegiatan Pilah dan Olah Sampah pada Kelompok PKK di Kota Salatiga - Prihtanti, Tinjung Mary; Widyawati, Nugraheni; Pudjihartati, Endang (Warta LPM, 2024)
Central Java province is the largest waste producer in Indonesia, with 4.25 million tons in 2022. Salatiga contributes quite a lot of waste in Central Java; according to data from the Salatiga City Communication and Information Service in 2018, organic waste (70%) and plastic (19%) were recorded. The objectives of the community service activity include increasing the housewives awareness, skills, and partnerships regarding the concept and actual practice of 3R (reduce, reuse, recycle). Activities include counseling, training, demonstrations, direct practice, Focus Group Discussion, mentoring, and evaluation of responses/output. The results of this activity conclude that the most significant potential waste from households in partner women groups (PKK) in Salatiga City is plastic waste, followed by food waste and waste from cooking activities. Community service activities trained and assisted in sorting and processing waste into economically valuable materials, namely compost, liquid organic fertilizer, artificial decorations, and various plastic creations, which received a positive response from the PKK group. The waste collection-sorting-deposit activity has been running in partner PKK groups up to 4 stages. However, only a few households have been involved due to a lack of time from family members, the hassle aspect, and the economic potential, which is not high enough. Processing organic waste into compost and POC, as well as inorganic waste into flower decoration creations, is an alternative application of the 3NG concept that housewives can carry out and is a PKK program. Interest in follow-up counseling and training is relatively high at a score of 4 on a scale of 1-5. This community service activity is expected to support national and global programs in improving care and the role of society in understanding waste management; community social entrepreneurship through processing waste into marketable products and education about environmental care to support a household-scale circular economy, supported by partnerships with external parties including Waste Bank (BSI) and the government.